The GIBACHT fellowship: a multilateral initiative for strengthening capacity in biosafety and biosecurity towards pandemic preparedness - Mertens, Eva; Zimmermann, Marlow; Dywicki, Janine; Lee, Min-Hi; Pelikan, Joachim; Bürkin, Barbara M.; Rutebemberwa, Elizeus; Hoffmann, Axel (Frontiers in Public Health, 2024)
The German Biosecurity Programme was launched in 2013 with the aim to support partner countries overcome biological threats including outbreaks or the intentional misuse of highly pathogenic agents. As part of this programme, this paper describes the development and implementation of a multilateral biosafety and biosecurity training initiative, called 'Global Partnership Initiated Biosecurity Academia for Controlling Health Threats' (GIBACHT).To achieve its objectives, GIBACHT implemented a blended-learning approach with selfdirected, distance-based learning phases and three training-of-trainer workshops. The programme follows Kirkpatrick's model of learning to guarantee sustainable effects of improved knowledge and skills. 109 fellows from 26 countries have been trained in seven cohorts. Many GIBACHT alumni have established additional biosafety/biosecurity trainings in their home countries. The knowledge exchange is strengthened by the implementation of a Moodle-based alumni network.GIBACHT has the potential to contribute to strengthening the capacities of partner countries in Africa, the Middle East, and South and Central Asia to respond and build resilience to biological threats.